2017
DOI: 10.1186/s41043-017-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of preschool children attending kindergartens in Kosovo

Abstract: BackgroundThere is very limited data on malnutrition of preschool children in Kosovo. The main objective of the study is to provide a nutritional status profile of preschool children attending kindergartens in Kosovo.MethodsCross-sectional study of children aged 12–59 months (n = 352 children) and children aged 60–83 months (n = 134) enrolled in public and private kindergartens of Kosovo. Anthropometric measurements used for this study are weight and height of the preschoolers (12–83 months). A measuring board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
5
3
Order By: Relevance
“…The obesity prevalence in our study was higher compared to the previous data collected in younger children in Kosovo in 2017 [ 10 ], which showed an obesity prevalence of 2,3%. The prevalence of overweight was also found to be higher compared to Rysha et al [ 10 ], who, however, operated a distinction between overweight (8,9%) and risk of being overweight (27,3%), by also referring to the 2006 WHO standards for infants and younger children. Our overweight and obesity prevalence data is in line with the overweight [ 14 ] and obesity [ 13 ] WHO prevalence data for the Serbian population aged 5–19 years.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The obesity prevalence in our study was higher compared to the previous data collected in younger children in Kosovo in 2017 [ 10 ], which showed an obesity prevalence of 2,3%. The prevalence of overweight was also found to be higher compared to Rysha et al [ 10 ], who, however, operated a distinction between overweight (8,9%) and risk of being overweight (27,3%), by also referring to the 2006 WHO standards for infants and younger children. Our overweight and obesity prevalence data is in line with the overweight [ 14 ] and obesity [ 13 ] WHO prevalence data for the Serbian population aged 5–19 years.…”
Section: Discussioncontrasting
confidence: 84%
“…By contrast, 1,2% stunting and 1,5% underweight subjects were found in our study, which suggests that malnutrition might be less prevalent nowadays. The undernutrition prevalence in our study was also lower than the 3% prevalence of stunting from a study performed in Kosovo in 2017 [ 10 ]. Although Kosovo remains one of the poorest countries in Europe, it has undergone a slow though progressive transition to better living conditions.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…After having a perusal of the previous studies, it is found that there is an anomaly in the age group selection for pre-school children in the studies of Indian settings as well as studies conducted in foreign countries (28,(32)(33)(34)(35)(36)(37)(38)(39). The age group ranges from 0-7 years in these studies.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Leaving aside the debate of age groups of pre-school children, this study surveyed the previous studies which investigated the risk factors of stunting among younger children. It has been found that individual child characteristics, e.g., child's age, sex, birth interval, birth order and birth weight are the associated factors of stunting (32,34,36,37,43,44). Many studies found that children born with low birth weight are more prone to become stunted in their childhood (45)(46)(47)(48)(49)(50)(51).…”
Section: Review Of the Literaturementioning
confidence: 99%